Transdisciplinarity in Financial Communication Writing for Target Readers - Whitehouse, Marlies (New Perspectives in Organizational Communication,, 2023)
This open access book identifies and analyses problems of text production in finance from three complementary perspectives: problem identification, problem analysis, and problem solution. By doing so, it explains why solving these problems in transdisciplinary collaboration benefits theory, practice, and society at large. Drawing on 25 years of ethnographic research, roughly 2100 text products, and more than 190 interviews with different stakeholders, it develops and evaluates measures to improve the communicative potential of financial texts and thereby make them accessible to professionals. The book will appeal to researchers and reflective practitioners in financial communication, organizational communication, financial analysis, investor relations, journalism, and applied linguistics. Marlies Whitehouse, PhD, head of Professorship in Professional Literacy at Zurich University of Applied Sciences (ZHAW), Switzerland. Her research fields and foci include applied linguistics, transdisciplinarity, professional literacy, financial communication, text production, and writing in the professions. She has extensive experience as writing and communication coach for national and international companies.